'Globalization, regional integration and the Economic Partnership Agreement : the social and labour dimensions' : report (ILO-SRO [Port of Spain]TT, 2008)
Deals with the aims and characteristics of the CARICOM Single Market and Economy and the provisions of the EPA, as they relate to the concerns of trade unions.
Keywords: REGIONAL INTEGRATION